2017
DOI: 10.1016/j.blre.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling pathway and its potential as a target for therapy in lymphoid neoplasms

Abstract: The NF-κB pathway, a critical regulator of apoptosis, plays a key role in many normal cellular functions. Genetic alterations and other mechanisms leading to constitutive activation of the NF-κB pathway contribute to cancer development, progression and therapy resistance by activation of downstream anti-apoptotic pathways, unfavorable microenvironment interactions, and gene dysregulation. Not surprisingly, given its importance to normal and cancer cell function, the NF-κB pathway has emerged as a target for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 170 publications
(197 reference statements)
1
65
0
1
Order By: Relevance
“…As expected, the phosphorylation levels of IκB α were also significantly increased in rumen epithelial cells treated with histamine. Subsequently, phosphorylation and proteasome-mediated degradation of IκB proteins would activate NF-κB and facilitate its transportation to nuclear [28]. This trend was observed, histamine significantly increased the protein and mRNA expression and transcriptional activity of NF-κB.…”
Section: Discussionmentioning
confidence: 68%
“…As expected, the phosphorylation levels of IκB α were also significantly increased in rumen epithelial cells treated with histamine. Subsequently, phosphorylation and proteasome-mediated degradation of IκB proteins would activate NF-κB and facilitate its transportation to nuclear [28]. This trend was observed, histamine significantly increased the protein and mRNA expression and transcriptional activity of NF-κB.…”
Section: Discussionmentioning
confidence: 68%
“…As a critical transcription factor, constitutive NF-κB activity was observed in a larger number of human cancers and promoted growth and progression, including that in prostate cancer [25,26,46]. In addition, HOTAIR expression was associated with induced proliferation and aggressive behavior of cancer cells, resulting in poor prognosis [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Given the tumor promoter roles of NF-κB [25,26] and LncRNA HOTAIR [20,21], we evaluated the effects of PPI with or without enzalutamide. We showed that PPI decreased NF-κB subunit p65 protein expression ( Fig.…”
Section: Ppi Decreased the Protein Expression Levels Of P65 And Lncrnmentioning
confidence: 99%
See 1 more Smart Citation
“…The target genes of the noncanonical NF-κB pathway function in lymphoid organogenesis, adaptive immunity, anti-inflammatory properties, and B-cell maturation. 1820 …”
Section: Oncogenic Signaling Pathways In Lymphomas and Their Thermentioning
confidence: 99%